Social support, empathy and compassion fatigue among clinical nurses: structural equation modeling - Jie Zhang; Xiao Wang; Ouying Chen; Juan Li; Yifei Li; Yiping Chen; Yaoyue Luo; Jingping Zhang (BMC, 2023)
Abstract Background Clinical nurses are at high risk for compassion fatigue. Empathy is a prerequisite for compassion fatigue, and social support is an important variable in the process of reducing individual stress. However, the role of social support in the relationship between empathy and compassion fatigue remains unclear. This study explored whether social support mediates the relationship between empathy and compassion fatigue among clinical nurses. Methods A total of 992 clinical nurses were recruited through convenience sampling for a cross-sectional study in Central China. They completed the General Information Questionnaire, Perceived Social Support Scale, Professional Quality of Life Scale, and Jefferson Scale of Empathy. SPSS was used to conduct descriptive statistical analyses. Pearson's or Spearman's correlation analyses and AMOS were employed to build a structural equation model (SEM) to verify the mediating effect of social support on the relationship between empathy and compassion fatigue. Results The results indicated that the standardized direct effect of empathy on compassion fatigue was 0.127, and the standardized indirect effect of empathy on compassion fatigue through social support was 0.136. The mediation effect ratio between empathy and compassion fatigue was 51.7%. Conclusions Our findings show that social support mediates the relationship between empathy and compassion fatigue among clinical nurses. This finding suggests that increasing nurses' social support can decrease the prevalence of compassion fatigue. Nursing managers should provide training related to flexibly adjusting empathy and educating nurses to establish effective social networks with family, friends, and colleagues to prevent compassion fatigue.